ADAPTING TO A CHANGING CLIMATE: PERUVIAN FARMERS' RESILIENCE - Pérez-Chávez, Juan Pablo; da Silva, Mariana; Sandra , García-Martínez (International Journal of Allied Research in Economics (IJARE), 2023)
The Indonesian retail sector is experiencing rapid growth, but the development of the furniture retail sector is hindered by supply chain-related problems. Supply chain management (SCM) is a business strategy that integrates the flow of materials, information, and finances through the entire supply chain. The successful implementation of SCM can improve the relationship between upstream suppliers and downstream customers, thus improving customers' satisfaction and company performance